2010
DOI: 10.3109/10242420903497354
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of (–)-maackiain byBeauveria bassianaandCunninghamella echinulatavar.elegans

Abstract: Maackiain (1) was transformed by Beauveria bassiana and Cunninghamella echinulata var. elegans to yield a new methylglycosylation product, (-)-maackiain-3-O-(4 -O-methyl--D-glucopyranoside) (2, 90%) and known trifolirhizin (3, 16%). The kinetics of the two glycosylation reactions was investigated. Additionally, 3 was converted to 2 via 4 -methylation by B. bassiana, which implied that the 4 -methylglycosylation mechanism of (-)-maackiain by B. bassiana is glycosylation followed by methylation. The antioxidant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Summarizing, the course of the biotransformation of isoflavones by three selected filamentous fungi known from their ability to O -glycosylation was investigated. High regioselectivity maintaining low substrate specificity was observed in biotransformation conducted by Beauveria bassiana , which is typical for this species and has been shown in previous studies [ 22 , 23 , 24 , 30 , 31 , 32 ]. Whilst, the substrate specificity of enzymes from Absidia genus is higher.…”
Section: Resultssupporting
confidence: 69%
“…Summarizing, the course of the biotransformation of isoflavones by three selected filamentous fungi known from their ability to O -glycosylation was investigated. High regioselectivity maintaining low substrate specificity was observed in biotransformation conducted by Beauveria bassiana , which is typical for this species and has been shown in previous studies [ 22 , 23 , 24 , 30 , 31 , 32 ]. Whilst, the substrate specificity of enzymes from Absidia genus is higher.…”
Section: Resultssupporting
confidence: 69%
“…bassiana , which resulted in obtaining a 4′-methylglucose derivative at a high yield (93%). This leads to the conclusion that 4′-methylglycosylation is a two-step process [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is able to catalyze wide range of reactions including hydroxylation, oxidation, reduction and hydrolysis [ 39 ]. It is also known that B. bassiana catalyzes reaction of glycosylation of numerous compounds by attaching 4- O -methylated derivative of glucopyranose to the substrate molecule [ 40 , 41 , 42 , 43 , 44 ]. Our previous studies showed that conjugation of 4- O -methyl-glucopyranose with prenylated and none-prenylated flavonoids was the major reaction in case of biotransformation conducted by B. bassiana [ 7 , 12 , 13 , 15 , 27 ] .…”
Section: Resultsmentioning
confidence: 99%